2005
DOI: 10.1556/abiol.56.2005.3-4.11
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the zinc-induced metallothionein protein with antibacterial activity in housefly larvae,Musca Domestica

Abstract: Three isoforms of metallothionein protein induced with Zinc were isolated and purified from housefly larvae, Musca domestica, by gel filtration on Sephadex G-75, G-25 and anion exchange on DEAE-52 chromatography. Among them, one was found to possess antibacterial activity, and was further characterized by SDS-polyacrylamide gel electrophoresis, sulphydryl group determination, enzyme hydrolysis, and spectra property. Our results showed that the novel protein has the characteristics of heat-stable, low-molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Since Crohn's disease is characterized by defective T cell apoptosis, whereas T cells from ulcerative colitis patients show a strong activation induced apoptosis, the role of MTs might be different in these two diseases. MTs have also been accredited antimicrobial properties [73, 74], which might be another relevant feature given the defective interaction of the host with the mucosal flora in IBD. Macrophages isolated from MTnull mice showed a significantly lower bactericidal effect on Staphylococcus aureus than macrophages from control mice.…”
Section: Mt Functions Relevant In Inflammation and Possibly In Infmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Crohn's disease is characterized by defective T cell apoptosis, whereas T cells from ulcerative colitis patients show a strong activation induced apoptosis, the role of MTs might be different in these two diseases. MTs have also been accredited antimicrobial properties [73, 74], which might be another relevant feature given the defective interaction of the host with the mucosal flora in IBD. Macrophages isolated from MTnull mice showed a significantly lower bactericidal effect on Staphylococcus aureus than macrophages from control mice.…”
Section: Mt Functions Relevant In Inflammation and Possibly In Infmentioning
confidence: 99%
“…Furthermore, LPS- and TNF- α -stimulated MT-null macrophages produced less NO than those from control mice, which was due to reduced activity of inducible NO synthase [73]. One MT isoform that was isolated and purified from housefly larvae had direct antibacterial effects on Escherichia coli as assayed by the plate growth inhibition assay [74]. …”
Section: Mt Functions Relevant In Inflammation and Possibly In Infmentioning
confidence: 99%
See 1 more Smart Citation
“…Various biological and medicinal activities of extracts from M. domestica larvae have been reported, e.g., antibacterial, antiviral, anti-allergic, antiinflammatory, antitumor, and radical scavenging activity (Meylaers et al 2004; Jin et al 2005; Liu et al 2011; Ratcliffea et al 2011). Our previous experiments also suggested that the homogenate of the larvae of this fly possessed antiviral activity against HbsAg and influenza viruses and hydroxyl radical scavenging activity in vi tro (Wang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence of metallothioneinlike toxins, and the high number of cysteine residues is used in the coordination of heavy metals rather than in the forming of disulfide bonds. However, antibacterial activity of a metallothionein protein expressed in housefly larvae has been reported recently, 17 possibly suggesting that the classification of metallothioneins as incorrect predictions may need to be reconsidered. The groups ICI, Toxin, Neurotoxin and Antibacterial are based on UniProt keywords.…”
Section: Classifier Evaluationmentioning
confidence: 99%